IMPROVING STUDENTS MOTIVATION AND LEARNING OUTCOMES IN SOCIAL SCIENCE LESSONS THROUGH POWTOON ANIMATION VIDEOS - Lusi Septi Rifdiani; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Learning media is one component that really supports improving the quality of learning. The purpose of this study was to determine whether the use of animated video media can improve the learning outcomes of class II students of SDIT Insan Cendekia Jeruk Gamping in social studies learning content. This research uses classroom action research method which consists of four stages, namely planning, action, observation, reflection. For data collection techniques using observation, interviews, tests and documentation. The data obtained were then analyzed using descriptive qualitative and quantitative statistical methods consisting of stages of data collection, data reduction, display or presentation of data, and the last one is drawing conclusions or verification. From this research, it shows that there is an increase in students' learning motivation from the pre-cycle stage to the second cycle. In addition, there was also an increase in the average student learning outcomes at the pre-cycle stage, cycle I, to cycle II seen from the average learning outcomes, normal gain values ??from pretest and posttest cycles I and II, as well as the number of students completed in class at this stage. pre-cycle, cycle I, to cycle II. Therefore, it can be concluded that the presence of animated video powtoon media can increase the motivation and learning outcomes of second grade students of SDIT Insan Cendekia Jeruk Gamping.